1999
DOI: 10.1021/ef9900435
|View full text |Cite
|
Sign up to set email alerts
|

Supercritical Fluid Extraction of Bal 150 Crude Oil Asphaltenes

Abstract: Supercritical fluid extractions (SFE) from BAL 150 asphaltenes were achieved with carbon dioxide as solvent under various experimental conditions (pressure, temperature, extraction time, and presence of cosolvent). SFE yields were between 5 and 12% of total asphaltenes. Extracts contained mainly linear alkanes (with chain lengths ranging from C14 to C30), various branched alkanes, and a multitude of complex branched and cyclic alkanes as shown by the GC/MS chromatograms. Many aromatic hydrocarbons, heteroaroma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(33 citation statements)
references
References 32 publications
4
29
0
Order By: Relevance
“…It has been found that, despite the polar nature of asphaltenes carbon dioxide is able to extract them from crude oil (28). However, in this work we did not determine if some asphaltenes present in the original Isthmus COTBS were extracted by supercritical ethane.…”
Section: Hydrocarbon Extraction From Crude Oil 2339mentioning
confidence: 65%
“…It has been found that, despite the polar nature of asphaltenes carbon dioxide is able to extract them from crude oil (28). However, in this work we did not determine if some asphaltenes present in the original Isthmus COTBS were extracted by supercritical ethane.…”
Section: Hydrocarbon Extraction From Crude Oil 2339mentioning
confidence: 65%
“…The high band intensity at 1232 cm −1 corresponds to the stretching vibration of C ar -O aromatic and/or in plane deformation of CO 2 H in carboxylic acids or unsaturated ethers [37][38][39][40]. The absorption band at 1114 cm −1 corresponds to the vibrations in ether (C sp3 -O-C ar ), alcohols (C sp3 -OH), C sp3 -OH of the carboxylic acids and C sp3 -O of ester [50] as well the large peak around 1040 cm −1 due to carbohydrates of polysaccharides [43,[51][52]. The 900-700 cm −1 range corresponds to the out of plane deformation in substituted phenolic [44], polar compounds and rocking of longue chains -(CH 2 ) n -.…”
Section: Fourier Transform Infrared Spectroscopy (Ftir)mentioning
confidence: 99%
“…The efficiency of CO 2 SFE crude oil extraction varied considerably with operating conditions: extraction mode (dynamic or static), solvent modifiers, and operating temperature and pressure [14]. Among these operating parameters, process temperature and pressure are predominant to extraction yield [15][16][17]. Although high pressure and low temperature are the preferred operating conditions for most CO 2 SFE systems, high temperature appeared to increase recovery of hydrocarbons from reservoir.…”
Section: Introductionmentioning
confidence: 99%